Reconstructing the Integration of Religion and Science through al-Attas’ Epistemology: A Deep Learning Instructional Model for Islamic Religious Education - Nursima, Nini; Amril, Amril (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to analyse Syed Muhammad Naquib al Attas epistemological framework on the integration of religion and science and to formulate its application within Islamic Religious Education in contemporary learning contexts in order to address knowledge fragmentation and support deep and meaningful learning. Methodology: This study uses a qualitative library research method. The data sources include primary works by Syed Muhammad Naquib al Attas, international peer reviewed journal articles, and selected IEEE indexed conference proceedings. Qualitative content analysis was employed, supported by Mendeley reference management software and document analysis techniques. Main Findings: This study identifies four core epistemological concepts in al Attas framework, namely human nature, knowledge, reason, and nature, grounded in a tawhid based worldview and guided by adab. Based on these concepts, a four component instructional model for Islamic Religious Education was formulated to support conceptual coherence and deep learning. Novelty/Originality of this study: This study introduces an operational instructional model that translates al Attas epistemological ideas into practical guidance for Islamic Religious Education. It advances existing scholarship by bridging classical Islamic epistemology with contemporary deep learning principles, offering a structured framework that addresses knowledge fragmentation and strengthens meaning oriented learning.